Pedagogical and Scientific Foundations of Teaching Texture and Surface Representation in Fine Arts Lessons - Qudratova Gulizuhro Otabek qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article analyzes the pedagogical and scientific foundations of teaching texture and surface representation in fine arts lessons. Correct application of texture and surface techniques enhances students’ visual expression, aesthetic taste, and creative abilities. The study examines the effectiveness of practical exercises, interactive technologies, and visual examples in learning texture and surface representation, emphasizing a combination of theoretical knowledge and practical skills.